Social Networks, Creators of Stereotypes - Angie Mariana Díaz Estupiñan (Enletawa Journal, 2022)
Social networks, nowadays, play an important role, particularly among young people. We live ina society that promotes specific ways of beauty, which become an example for many, who want tofollow them to fit into today's world. In social networks, such as Instagram or Facebook, the pressurethat is imposed through beauty stereotypes is hard. Several users upload photos looking like they havea perfect life. Women normalize thinness as the perfect body type, but that is a lie to most people.There is no doubt that young people, who use social media the most, have a serious problem gettingcarried away by what they see on the internet.